Quality of life and need assessment changes in individuals with severe mental illness: A 5-year follow-up study. - Dr., Freydís Jóna Freysteinsdóttir (International Journal of Psychosocial Rehabilitation, 2015)
The present study is a 5-year follow-up study of patients with schizophrenia and mood disorders, who were patients on a day-clinic in Landspitali University Hospital, Reykjavik, Iceland for more than one year in 2008. In all, 47 patients fulfilled the criteria and were interviewed that year at a baseline. Their needs were independently rated by themselves and by their key-worker. The interview with the patients also included quality of life assessed by the Lancashire Quality of Life Profile (LQoLP) which includes the Rosenberg self-esteem scale.. Five years later, 30 of them also participated in this follow up study, but in the meantime the day-clinic had been closed tvo years be- fore follow-up. Over the 5-year follow–up quality of life of the subjects had deteroriated (-0.28) although not stat- istically significant owing to the small sample size and they had more unmet needs (+0.4). At follow-up one third of the subjects reported that they had no reliable friend and quarter of them had no close friend. Quality of life cor- related with few unmet needs to a minor extent and more strongly with the level of self-esteem.